"GET-UP" study rationale and protocol: a cluster randomised controlled trial to evaluate the effects of reduced sitting on toddlers' cognitive development. Issue 1 (December 2016) - Santos, Rute; Cliff, Dylan; Howard, Steven; Veldman, Sanne; Wright, Ian; Sousa-Sá, Eduarda; Pereira, João; Okely, Anthony
Abstract Background The educational and cognitive differences associated with low socioeconomic status begin early in life and tend to persist throughout life. Coupled with the finding that levels of sedentary time are negatively associated with cognitive development, and time spent active tends to be lower in disadvantaged circumstances, this highlights the need for interventions that reduce the amount of time children spend sitting and sedentary during childcare. The proposed study aims to assess the effects of reducing sitting time during Early Childhood Education and Care (ECEC) services on cognitive development in toddlers from low socio-economic families. Methods/Design We will implement a 12-months 2-arm parallel group cluster randomised controlled trial (RCT) with Australian toddlers, aged 12 to 26 months at baseline. Educators from the ECEC services allocated to the intervention group will receive professional development on how to reduce sitting time while children attend ECEC. Participants' cognitive development will be assessed as a primary outcome, at baseline and post-intervention, using the cognitive sub-test from the Bayley Scales of Infant and Toddler Development. Discussion This trial has the potential to inform programs and policies designed to optimize developmental and health outcomes in toddlers, specifically in those from disadvantaged backgrounds. Trial registration Australian New Zealand Clinical Trials Registry:ACTRN12616000471482, 11/04/2016, retrospectively registered.